Infectious disease clinics of North America : biologic response modifiers in infectious disease - Amital, Howard; Bergman, Scott;Ferguson, Mckenzie C.;Hsu, Jennifer L.;Kak, Vivek;Khardori, Nancy Misri;Khardori, Romesh;Koirala, Janak;Khardori, Nancy Misri ;Moellering, Jr., Robert C. (Philadelphia, Pennsylvania : Saunders an imprint of Elsevier, Inc., 2011)
Biologic response modifiers (BRMs) are substances that stimulate the body's response to infection and disease. The body naturally produces small amounts of these substances. Scientists can produce some of them in the laboratory in large amounts for use in treating infections and other diseases. This issue reviews the use of BRMs to treat infectious diseases as well as the infectious complications of BRMs used to treat non-infectious diseases. Articles on vaccines, antibodies, interferon, and other substances are included.
Biologic Response Modifiers: Relevance & Repercussions -- Overview of Biologic Response Modifiers in Infectious Disease -- Role of Endogenous Biological Response Modifiers in Pathogenesis of Infectious Disease -- Vaccines and Vaccine Adjuvants as Biological Response Modifiers -- Polyclonal Immunoglobulins and Hyperimmune Globulisms in Prevention and Management of Infectious Diseases -- Monoclonal Antibodies in Infectious Diseases: Clinical Pipeline in 2011 -- Colony-Stimulating Factors in the Prevention and Management of Infectious Diseases -- Interferons as Therapeutic Agents for Infectious Diseases -- Mediators of Systematic Inflammatory Response Syndrome and the Role of Recombinant Activated Protein C in Sepsis Syndrome -- The Common Immunogenic Etiology of Chronic Fatigue Syndrome: From Infections to Vaccines via Adjuvants to the ASIA Syndrome -- Mycobacteria and Biological Resopnse Modifiers: Two Sides of the Relationship -- Biologics and Infections: Lessons from Tumor Necrosis Factor Blocking Agents -- Index.
Includes index.
Keywords: BIOLOGICAL RESPONSE MODIFIERS